Gender difference in clinical conditions among hospitalized adults with myotonic dystrophy. Issue 3 (13th January 2019) - Ouyang, Lijing; Wang, Yinding; Valdez, Rodolfo; Johnson, Nicholas; Gutmann, Laurie; Street, Natalie; Bolen, Julie
ABSTRACT: Introduction : In this study we examined gender differences in adult hospitalizations with myotonic dystrophy (DM). Methods : From the Nationwide Inpatient Sample (NIS) 2010–2014, we identified 1, 891 adult hospitalizations with a DM diagnosis and constructed a comparison group of hospitalizations without DM using propensity score matching. We calculated relative risk by gender for 44 clinical diagnoses that each accounted for at least 5% of DM hospitalizations. Results : Hospitalizations with DM were longer (4.8 vs. 4.1 days, P < 0.0001) and more costly ($13, 241 vs. $11, 458, P < 0.0001) than those without DM. More than half (25 of 44) of the conditions co‐occurring with DM hospitalizations did not differ in their relative risks by gender. For those that differed by gender, only 5 were specific to DM, compared with hospitalizations without DM. Discussion : Our findings highlight the importance of comprehensive and coordinated care for DM rather than gender‐oriented care in the inpatient setting. Muscle Nerve 59 :348–353, 2019